A rapid microwave induced synthesis of isonicotinamide derivatives and their antifungal activity - Bušić, Valentina; Vrandečić, Karolina; Siber, Tamara; Roca, Sunčica; Vikić-Topić, Dražen; Gašo-Sokač, Dajana (2019)
Ten novel isonicotinamide derivatives were prepared by quaternization reactions of isonicotinamide with methyl iodide and nine differently substituted 2 bromoacetophenones under rapid microwave irradiation of 10 minutes. The microwave preparations were significantly faster and with yields higher up to 8 times, than the preparations by conventional method. The structures of synthesized molecules were determined by one- and two dimensional NMR and IR spectroscopy, mass spectrometry and elemental analysis. Antifungal activity of all compounds was tested in two different concentrations (10 and 100 µg mL–1) against Fusarium oxysporum, Fusarium culmorum, Macrophomina phaseolina and Sclerotinia sclerotiorum in vitro. From the antifungal assay it can be seen that the most prepared compounds have moderate to weak activity against M. phaseolina and F. culmorum. A very high inhibitory rate was observed against S. sclerotiorum, 62–87.5 % in concentration of 10 µg mL–1 and 83.7–93.2 % in concentration of 100 µg mL–1.
Bibliografija: 41 jed.
Summary.
Keywords: Derivati izonikotinamida -- Sinteza -- Antifungalna aktivnost -- Mikrovalno zračenje